If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2s + 6 = -3s Reorder the terms: 6 + -2s = -3s Solving 6 + -2s = -3s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '3s' to each side of the equation. 6 + -2s + 3s = -3s + 3s Combine like terms: -2s + 3s = 1s 6 + 1s = -3s + 3s Combine like terms: -3s + 3s = 0 6 + 1s = 0 Add '-6' to each side of the equation. 6 + -6 + 1s = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 1s = 0 + -6 1s = 0 + -6 Combine like terms: 0 + -6 = -6 1s = -6 Divide each side by '1'. s = -6 Simplifying s = -6
| 6(x+2)=10 | | (2a^2-4a-16)= | | 5u-15=20 | | (2b^2+4a+4)= | | .4+2=24 | | 3p-5=3(p+1) | | -4(1-x)=-6-6x | | x^2+1x-3=0 | | 6x+.11=7x+.77 | | C=85h | | x*(x-4)=165 | | (3b^2-9b-12)= | | 4m+7=7(m-2) | | 18p+14q=p-7-4p | | 12x-6=(-48) | | 6(x-2)=10(x-3)-12 | | x*(x+4)=165 | | (4/3)-(2x/3) | | 2c+5=4c-9 | | -1-3f=-2-3f | | (2a^2+2a-112)= | | 5(w-9+4w-1)=-65-2(4-w) | | 1.5x+2y=72 | | -3-7r=-6-7r | | 5cos^2(x)+2cos(x)=0 | | 5cos^2x+2cosx=0 | | 1.36x+2=0.36x+4 | | 1.36x+2=0.36+4 | | -10b-6=-4-10b | | 5+e^1-2x=36 | | (-2x^2)+x-1=0 | | X=40-y |